The Influence of Monas Tourism Amenities and Accessibility Services on Senior-Friendly Tourism in Jakarta - Juliet Sutedja; Rudy Pramono (Publikasi Indonesia, 2024)
The Jakarta National Monument is a monument that is a characteristic of the city of Jakarta. The National Monument offers a tourist attraction in the form of history about the struggle of the Indonesian nation. This study aims to analyze the extent of the influence of service quality and access to elderly tourism support at Mona's. The method used in this study is qualitative. The data sources in this study were obtained through interviews, observations, questionnaires and literature from previous research or journals. From the results that have been obtained by the author, it can be concluded that Monas can still be developed in terms of access and facilities, unfortunately, for now, Monas are still not friendly to elderly tourists who still need a lot of special facilities and access to run and can also enjoy tourist activities at Mona's. It can be concluded that tourism for the elderly is still very minimally done, but elderly tourism is one of the aspects that can be profitable if more is worked on.